Understanding organizational change management: the role of micro and macro influences. Issue 1 (16th November 2020) - Harden, Erika; Ford, Lucy R.; Pattie, Marshall; Lanier, Patricia
Abstract : Purpose: In response to external conditions, organizations yearn to gain a competitive edge during unremitting change. Recognizing the importance of managing change, researchers have aggressively investigated organizational change at the macro level. This research, however, argues that an employee's ability to cope with change is a function of both micro (individual) and macro (contextual) factors. Design/methodology/approach: The survey data were collected at an organization that was undergoing a significant internal change. Correlational and structural equation modeling techniques were used for data analysis. Findings: The results suggest that individual differences (intolerance for ambiguity) and contextual factors (LMX, TMX receipts and TMX contributions) are important factors for understanding the ability to manage organizational change effectively. Additionally, it is argued that contextual factors not only have direct effects on coping with change but indirect effects through perceptions of work group effectiveness. Our results indicate that both micro and macro factors are important for understanding the ability to cope with and manage change. Research limitations/implications: The research leaves open some interesting questions around the role of contextual factors in coping with change, in addition to the interaction with individual differences. Practical implications: Most sources discuss change as focused at the organizational level. Managers will be well served to understand that the degree to which employees cope effectively with change will be partly determined by the interaction of individual differences and the organizational and team level context. Originality/value: This research extends our understanding of the relationship between social exchange relationships and how individuals cope with change in organizations and the mechanism by which that occurs.